Avaliação do índice termodinâmico Gálvez-Davison na previsibilidade pluviométrica na cidade de Belém-PA - LOBATO, Richard Reno da Costa (2020)
The Gálvez-Davison Index (GDI) was developed to improve the prediction of tropical convection, due to the limited efficiency of traditional instability indices, when used for tropical regions. The GDI considers thermodynamic properties of the low and medium troposphere, and is calculated from ambient temperatures and mixing ratios available at 950, 850, 700 and 500 hPa. Thus, it can be easily obtained from radiosonde data, grid analysis and numerical model output. This study aimed to evaluate the performance of GDI in the predictability of precipitation in Belém-PA, from January 2009 to December 2018, compared to the performance of other thermodynamic indices. To evaluate the ability of the thermodynamic indices to predict the occurrence of precipitation in Belém, within eight hours after the launching of the radiosonde, the contingency analysis method (MAC) was used. The MAC uses prediction error and accuracy criteria to assess its performance, using forecast indexes, which are calculated using parameters in the Contingency table. The results obtained show that the K index had the best performance among the studied indexes, the GDI obtained the second best performance. SWEAT was the worst index evaluated in this study. Regarding the analysis by period, the GDI performed better than the other indexes at 00 UTC, in the other periods the K index showed better efficiency. In general, the period of the year and time of day when the thermodynamic indices performed best, was in the rainy season at 12 UTC. Their worst performance, on the other hand, occurred in the least rainy season at 00 UTC. The case studies for February 3 and July 3, 2018 showed that the K and GDI indices were able to predict the precipitating events that occurred on those days. This shows that the K and GDI indexes are the most reliable to be used in predicting rainfall in the Belém region.